Evaluation of TALIS 2018 Results in the Context of Professional Development: Turkey Sample - Ümit Kahraman; Osman Tayyar Çelik (Athens Institute for Education and Research, 2022)
In this research, participation in professional development (PD) activities, perceptions of PD needs and barriers for PD, and differences in terms of seniority were examined in Turkey sample based on the Teaching and Learning International Survey (TALIS) 2018 data. A total of 15,498 teachers, including 3,204 primary school teachers, 3,952 secondary school teachers and 8,342 high school teachers, were included in the sample of the study. The results of the research show that teachers participate more in-service trainings within the scope of mandatory PD policies. Peer observation, coaching, and observation visits to workplaces, public institutions or non-governmental organizations and other schools are the least PD activities that teachers participate. Teachers need PD more in the field of teaching students with special needs and in multicultural or multilingual environments. According to teachers, the biggest barriers to PD are the lack of any incentives and support to participate in PD, incompatibility with the work schedule and the lack of appropriate PD activity. In addition, PD activities that teachers participate in, PD needs and barriers to PD are significantly different in terms of seniority. The results were discussed in terms of PD literature and Turkey context and suggestions have been made based on the results.